Identifying putative allergens from Cenostigma pluviosum pollen using proteomic bioinformatics - Olbrich Neto, Jaime; Mendonça, Bruna Cavecci; Olbrich, Sandra Regina Leite Rosa; Rocha, Francielle Ramalho; Clemente, Eloisa Fornaro; Rossini, Bruno Cesar; Santos, Lucilene Delazari dos (Springer Nature, 2024)
Background: Routinely, signs and symptoms of pollinosis worsen during the flowering period of the Cenostigma pluviosum var. peltophoroides (Sibipiruna) trees. This study aimed to determine whether Sibipiruna pollen contains allergenic proteins. Methods and Results: The pollen from mature Sibipiruna anthers was morphologically characterized using optical, scanning electron and emission microscopy. Additionally, biochemical characterization was conducted through Shotgun Label-Free Proteomic Analysis. Three hundred and forty-nine proteins were identified using the UNIPROT database and thirty-six were confirmed as homologous allergenic proteins in the Allergome database. Conclusions: At the first time, Sibipiruna pollen allergenic proteins have been described and this study provides a deeper understanding of the allergenic proteins present in this pollen. These preliminary findings can be useful to assist in the development of targeted extracts for the study of sensitization and potential immunotherapy in the future.